Adsorpsi Zat Warna Remazol Brilliant Blue R dengan Adsorben Arang Aktif dari Kayu Kopi (Coffea sp.) - Bella Puja Prismalasari; I Nyoman Sukarta; Made Vivi Oviantari (Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to evaluate the characteristics, adsorption efficiency, and parameters of adsorption isotherm of Remazol Brilliant Blue R dye using coffee wood activated charcoal. The adsorbent was synthesized through a manual charring process followed by chemical activation using CaCl2. Adsorbent characterization includes proximate analysis using Thermogravimetric Analysis (TGA) and surface morphology observation using Scanning Electron Microscope-EDX (SEM-EDX). The results of the proximate analysis showed volatile matter 31.223%, water content 12.21%, ash content 3.06%, total fixed carbon 53.50% and iodine number of 368.097 mg/g. Meanwhile, the activated charcoal CaCl2 has a volatile matter analysis result of 27.17%, water content of 19.90%, ash content of 11.66%, total fixed carbon of 41.28%, and iodine number of 387.1365 mg/g. The surface morphology of the activated charcoal with CaCl2, qualitatively has more cavities than the unactivated charcoal. Effective efficiency if carried out using activated charcoal with CaCl2 at a contact time of 105 minutes (%E = 28.5737), pH 4 (%E = 36.3948), and a concentration of 20 mg/L (%E = 31.8081). This absorption mechanism follows the Langmuir isotherm pattern.